PENGARUH SUASANA DAN KEBERSIHAN TERHADAP KEPUASAN PELANGGAN DI KASTA COFFEE & RESTO BATU AJI BATAM - Etika Refikanzyah; Moh. Thandzir (Puslitabmas Batam Tourism Polytecnic, 2026)
This study aims to examine the influence of atmosphere and cleanliness on customer satisfaction at Kasta Coffee & Resto Batu Aji, Batam. The background of this research is based on the rapid development of the culinary industry and the increasing lifestyle of people who enjoy spending leisure time in cafes. Customers no longer seek only good taste but also a complete dining experience. Therefore, atmosphere and cleanliness play an important role in creating customer satisfaction. The research problem focuses on whether atmosphere and cleanliness partially and simultaneously affect customer satisfaction. This study uses a quantitative method with a probability sampling technique. The population consisted of 6,728 customers from May to June 2025, and the sample of 100 respondents was determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires distributed to customers of Kasta Coffee & Resto Batu Aji Batam and then analyzed using SPSS version 25. The results show that atmosphere has a positive and significant influence on customer satisfaction. Cleanliness also has a positive and significant influence on customer satisfaction. Simultaneously, both atmosphere and cleanliness significantly affect customer satisfaction. The coefficient of determination (R²) value of 0.636 indicates that 63.6% of customer satisfaction is explained by atmosphere and cleanliness, while the remaining 36.4% is explained by other factors not examined in this study. In conclusion, to improve customer satisfaction, Kasta Coffee & Resto Batu Aji Batam should maintain a consistent atmosphere, especially during peak hours, and enhance cleanliness in public areas such as dining tables, floors, outdoor areas, and restrooms